The effect of job stress and work-family conflict on Nurses Turnover Intention - Ayudhia, Maharani; Febrianti, Adjeng Mariana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Turnover the intention of hospital employees, especially nurses, is currently a challenge that is of concern. This study uses a quantitative approach to determine the factors that influence the high turnover intention of nurses. Specifically, the researcher considers the role of job stress and work-family conflict as antecedents of turnover intention. Data were taken through a survey by distributing questionnaires to respondents, with a total sample of 90 nurses. Each item in the questionnaire was measured using a Likert scale with five points. The data obtained were processed using multiple regression analysis with software. The results of this study confirmed the hypothesis proposed by the researcher, that job stress and work-family conflict felt by nurses could increase their intention or desire to leave their job at the hospital. The findings of this study can be used as a consideration and reference for managers, leaders, and supervisors in hospitals to pay attention to the conditions of stress and work-family conflict that are being experienced by employees.